PENERTIBAN PEDAGANG MOBIL KELILING OLEH SATUAN POLISI PAMONG PRAJA DI KOTA PEKANBARU TAHUN 2017-2018 - Gladissa Ivanda R.; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The program for setting up and guiding mobile car traders in the city of Pekanbaru is still not optimal with the achievement of specified targets, it can be seen from the program of setting up and guiding the mobile car traders carried out by the Civil Service Police Unit in the city of Pekanbaru not as expected still selling mobile car merchants despite raids and warning letters.The formulation of the problem in this study is how is the enforcement of mobile car traders by the Civil Service Police Unit in Pekanbaru City 2017-2018. The purpose of this study is to find out and analyze the enforcement of mobile car dealers by the Civil Service Police Unit in Pekanbaru City in 2017-2018 and its obstacles.The results of this study are Based on the results of the research that has been done, the conclusion of the researchers regarding the implementation of the task of the Civil Service Police Unit in controlling mobile car dealers in the city of Pekanbaru is quite accomplished. The obstacle found in this study is the absence of regulations specifically regulating mobile car traders, while currently the authority of the Pekanbaru Civil Service Satpol in controlling mobile car dealers who violate public order only refers to the Pekanbaru City Regulation on Public Order so that this makes the role of the Pekanbaru City Civil Service Satpol very limited. In addition, the still weak coordination between the Civil Service Satpol of the City of Pekanbaru and the Pekanbaru City Market Service were also very influential factors in determining the participation of the Pekanbaru Civil Service Satpol in maintaining public order in Pekanbaru City.Keywords: Ordering, Mobile Car Traders